2020
DOI: 10.47836/pjtas.43.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Performance in Improved ‘KDML105’ Rice (Oryza sativa L.) Lines Containing Drought and Salt Tolerance Genes under Drought and Salt Stress

Abstract: Rice (Oryza sativa L.) ‘KDML105’ is the most popular aromatic rice originating in Thailand. This cultivar is highly susceptible to abiotic stresses, especially drought and salt stress during the seedling stage. The objective of this study was to investigate the photosynthetic performance in response to drought and salt stress of four improved breeding lines, specifically CSSL94 and CSSL103 (containing drought-tolerant quantitative trait loci: DT-QTLs) and RGD1 and RGD4 (containing a salt-tolerance gene, SKC1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Non-significant differences in chlorophyll fluorescence on Tubtim Chumphae rice seedlings and early vegetative stage in this study concurred with previous reports that this occurrence indicated that PSII was unaffected by salinity stress 30 . However, previous studies reported that salinity stress decreased chlorophyll fluorescence in many plant species such as rice 31 and wheat 32 .…”
Section: Discussionmentioning
confidence: 89%
“…Non-significant differences in chlorophyll fluorescence on Tubtim Chumphae rice seedlings and early vegetative stage in this study concurred with previous reports that this occurrence indicated that PSII was unaffected by salinity stress 30 . However, previous studies reported that salinity stress decreased chlorophyll fluorescence in many plant species such as rice 31 and wheat 32 .…”
Section: Discussionmentioning
confidence: 89%
“…The parent DH103 is a rice variety derived from a double haploid (DH) population from a cross between an indica variety, IR62266, and a japonica variety, CT9993 [49]. DH103 has been used as a donor for several abiotic stresses, e.g., drought tolerance and salt tolerance [50]. However, the use of this rice variety for dirty panicle disease resistance has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of various plant tissues to retain K + under stress conditions has been recognized as a novel and essential mechanism of salinity stress tolerance in plants (Shabala et al, 2016;Wu et al, 2018). W hile K + limitation in rice decreases net photosynthetic rate and stomatal conductance damaging PS-II reactions (Pamuta et al, 2020). Nonetheless, sodium-potassium ratio determines their synergistic or antagonistic response.…”
Section: Introductionmentioning
confidence: 99%